Description of electroneuromiographic and laboratorial findings in leprosy neuropathy, according to its clinical forms: the confirmation of a spectral disease - Santos, Diogo Fernandes dos; Borges, Isabella Sabião; Garcia, Leonardo Peixoto; Antunes, Douglas Eulálio; Luppi, Andrea De Martino; Goulart, Isabela Maria Bernardes (Frontiers in Medicine, 2024)
Introduction Leprosy is one of the most common infectious cause of peripheral neuropathy in the world and can lead to sequelae and physical disabilities. Electroneuromyography (ENMG) is the gold-standard test for evaluating neural impairment, detecting from subclinical abnormalities to advanced lesions. This study aims to describe the electroneuromyographic findings in patients with leprosy, according to their clinical forms. Methods The study is a retrospective observational analysis of the medical records of patients with leprosy, of a National Reference Center of Sanitary Dermatology and Leprosy in Brazil between 2014 and 2022. 513 patients underwent ENMG at leprosy diagnosis and also underwent a clinical, serological and molecular evaluation of the disease. Results The electroneuromyographic findings showed 2,671 altered nerves, with an average of 6.9 (±5.1) altered nerves per patient. The most affected sensory nerves were the superficial peroneal (25.0%; 413/1649), sural (15.1%; 397/2627) and ulnar (13.8%; 363/2627), with average of 4.3 (±3.2) affected sensory nerves per patient. The most affected motor nerves were the ulnar (33.1%; 338/1022) and common peroneal (12.1%; 319/2627), with average of 2.6 (±2.5) motor nerves affected per patient. 126 patients presented normal ENMG and, among the 387 with abnormalities in the exam, 13.2% (51/387) had mononeuropathy and 86.8% (336/387) had multiple mononeuropathy. Axonal involvement was more frequent in primary neural leprosy, borderline-tuberculoid, borderline-lepromatous and lepromatous forms. Discussion Our findings support that leprosy is a spectral disease, characterized by a balance between host immunity and bacillary load. Therefore, the impairment and electroneuromyographic characteristics are distinct and may vary according to the clinical form.